PENGARUH LATIHAN JUMP TO BOX TERHADAP POWER OTOT TUNGKAI PADA CLUB SIBAM KARATE PEKANBARU - Loyo C. Panggabean; Ramadi Ramadi; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that their strength is very low, and it may also cause them to perform poorly. Because without good power, the technique itself is not enough to win the match. The title of this research is "the effect of jumping into the training box on leg strength at the Pekanbaru Sibate karate club", so that the goals of future athletes can perform and play much better. The form of this research is (a group of pre-test-post-test design) with Doam Sibam Karate team population in Pekanbaru. the data in this study were all populations of 6 people. The tool used in this research was to use a vertical jump test, which aims to find out how much of an impact the leg muscle has. to test the normality with the Lilifour test at a significance level of 0.05α. Based on the analysis of normality test data X, it produces Lhitung 0.138 and Ltable 0.319, which means Lhitung <Ltable. while the variable Y gives Lhitung 0.153 and L table 0.319. This means Lhitung <L Table. then the data is normally distributed. It can therefore be concluded that for the effect of variable x with variable y the value of t = 4.556, then t arithmetic> t table (4.556)> (2.015), then Ha is accepted, in other words there is a significant effect on the effect of jumping in the training box on the strength of karate Sibam Dojo Pekanbaru leg muscle athlete.Key Words: Jump To Box Exercise, Leg Muscle Strength